2014
DOI: 10.7448/ias.17.1.18646
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of men to virologic failure during antiretroviral therapy in a public routine clinic in Burkina Faso

Abstract: IntroductionGender differences in antiretroviral therapy (ART) outcomes are critical in sub-Saharan Africa. We assessed the association between gender and virologic failure among adult patients treated in a public routine clinic (one of the largest in West Africa) in Burkina Faso.MethodsWe performed a case-control study between July and October 2012 among patients who had received ART at the Bobo Dioulasso Day Care Unit. Patients were eligible if they were 15 years or older, positive for HIV-1 or HIV-1+2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
27
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 36 publications
14
27
6
1
Order By: Relevance
“…Taking advantage of this situation, we assessed the impact of older age on virological suppression and found that being ≥ 50 years of age was significantly associated with a better virological outcome (aOR 1.74; 95% CI 1.20–2.53; P = 0.003). This result is in line with previous studies using age either as a continuous variable or as a categorical variable with lower thresholds . The better virological outcome in older patients on ART might be linked to improved socioeconomic and psychological status.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taking advantage of this situation, we assessed the impact of older age on virological suppression and found that being ≥ 50 years of age was significantly associated with a better virological outcome (aOR 1.74; 95% CI 1.20–2.53; P = 0.003). This result is in line with previous studies using age either as a continuous variable or as a categorical variable with lower thresholds . The better virological outcome in older patients on ART might be linked to improved socioeconomic and psychological status.…”
Section: Discussionsupporting
confidence: 91%
“…20-2.53; P = 0.003). This result is in line with previous studies using age either as a continuous variable or as a categorical variable with lower thresholds [13][14][15][16]. The better virological outcome in older patients on ART might be linked to improved socioeconomic and psychological status.…”
Section: Discussionsupporting
confidence: 91%
“…Virological failure in our series was 19%. This prevalence is like the one described by Boender (20) in countries with limited resources, and lower than those described in the sub-region precisely in Togo [21] and Burkina-Faso [22].…”
Section: Discussionsupporting
confidence: 78%
“…17,18 Given the men's strong preference for HIV clinics as their source of FP services, we argue that integrating FP services into HIV clinics should be kept a priority as this model likely fosters male involvement in FP, which, in turn, may improve contraceptive use. 29 In addition, HIVpositive men in SSA tend to have worse clinical outcomes as compared to women [39][40][41][42][43][44][45] and face unique challenges in accessing and remaining in HIV care and treatment, [46][47][48][49][50] and integrated FP services may serve as one of many tools to attract and retain these men.…”
Section: Discussionmentioning
confidence: 99%